2013
DOI: 10.1016/j.ophtha.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Domain Optical Coherence Tomography Characteristics of Intermediate Age-related Macular Degeneration

Abstract: Purpose Describe qualitative spectral-domain optical coherence tomography (SD-OCT) characteristics of eyes classified as intermediate age-related macular degeneration (nonadvanced AMD) from Age-Related Eye Disease Study 2 (AREDS2) color fundus photography (CFP) grading. Design Prospective cross-sectional study. Participants We included 345 AREDS2 participants from 4 study centers and 122 control participants who lack CFP features of intermediate AMD. Methods Both eyes were imaged with SD-OCT and CFP. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 44 publications
4
120
0
1
Order By: Relevance
“…5,8,20,21 This hypothesis was supported by some laboratory studies that demonstrated the potential ability of RPE cells to migrate when induced by cytokines and other inflammatory mediators in response to oxidative damage and complement activation. 22,23 Previous studies 7,24 showed that HRF in AMD were associated or colocalized with the drusen apex and showed an increased association with RPE atrophy at baseline, 24 or if atrophy was not already present, with an increased risk of developing atrophy at that location. 7 Christenbury et al 8 suggested that the association between HRF and drusen becomes more significant over time with an increasing number of HRF associated with increasing drusen and atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,20,21 This hypothesis was supported by some laboratory studies that demonstrated the potential ability of RPE cells to migrate when induced by cytokines and other inflammatory mediators in response to oxidative damage and complement activation. 22,23 Previous studies 7,24 showed that HRF in AMD were associated or colocalized with the drusen apex and showed an increased association with RPE atrophy at baseline, 24 or if atrophy was not already present, with an increased risk of developing atrophy at that location. 7 Christenbury et al 8 suggested that the association between HRF and drusen becomes more significant over time with an increasing number of HRF associated with increasing drusen and atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…29 A better classification that becomes widely established would be also helpful for interpretation of other potential precursor lesions that have been recently described by SD-OCT, such as thinning of retinal layers in the presence of drusen regression, evolution of HRF, and disintegrated RPE dots. 23,[26][27][28][47][48][49][50][51] Various limitations of this study need to be considered. The number of included subjects is relatively small, and a substantial high number of subjects dropped out of this natural history study (a total of 32.7% at year 6).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Furthermore, the largest ongoing randomized trial for age-related macular degeneration (AMD), the NEI-sponsored Age-Related Eye Disease Study 2, exclusively allows the Bioptigen SDOIS platform for its longitudinal, observational ancillary SDOCT study (AREDS2 Ancillary SDOCT Study). 6,26 The baseline dataset and measurements for both control and AMD eyes in this study has been made publicly available. 6 Several studies have concluded that comparing retinal thickness with instruments from different manufacturers is not advised for clinical studies.…”
Section: -10mentioning
confidence: 99%